A new oxidatively stable ligand for the chiral functionalization of amino acids in Ni(II)–Schiff base complexes - Dmitrieva, Alena V.; Levitskiy, Oleg A.; Grishin, Yuri K.; Magdesieva, Tatiana V. (Beilstein Journal of Organic Chemistry, 2023)
A new oxidatively stable (S)-N-benzylproline-derived ligand ((S)-N-(2-benzoyl-5-tert-butylphenyl)-1-benzylpyrrolidine-2-carboxamide) and its Ni(II)–Schiff base complexes formed of glycine, serine, and dehydroalanine are reported. A bulky tert-butyl substituent in the phenylene fragment precludes unwanted oxidative dimerization of the Schiff base complex, making it suitable for targeted electrochemically induced oxidative modification of the amino acid side chain. Experimental and DFT studies showed that the additional tert-butyl group increases the dispersion interactions in the Ni coordination environment making the complexes more conformationally rigid and provides a higher level of thermodynamically controlled stereoselectivity as compared to the parent Belokon complex. Additionally, functionalization with the tert-butyl group significantly enhances the reactivity of the deprotonated glycine complex towards electrophiles as compared to the anionic species formed from the original Belokon complex. Solubility of the t-Bu-containing ligand and its Schiff base complexes is increased, facilitating scaling-up the reaction procedure and isolation of the functionalized amino acid.
Keywords: asymmetric synthesis; chiral auxiliaries; cysteine derivatives; Ni–Schiff base complexes; voltammetry testing